Early evidence for establishment of a Chinook salmon population in a restored watershed - Lauren G. Hitt; Malte Willmes; George Whitman; Mackenzie C. Miner; Carson Jeffres; Rachel C. Johnson; Dennis E. Cocherell; Nann A. Fangue; Andrew L. Rypel (Ecosphere)
Abstract As fish populations face compounding pressures under climate change, highly modified rivers are receiving increasing research and conservation attention as important sites for restoration. Across the North Pacific Ocean, Chinook salmon (Oncorhynchus tshawytscha) have experienced unprecedented declines and extirpations because of habitat loss and fragmentation and climate variability. Here, we studied a rare example of a novel salmon population developing in Putah Creek, California, a dam‐controlled stream flowing through an area of intensive agriculture where salmon were unlikely to occur prior to the rehabilitation of a more natural flow regime. We used otoliths from adult Chinook salmon carcasses recovered from Putah Creek to determine river or hatchery of origin for five spawning year classes. Our results provide evidence of successful salmon reproduction, outmigration survival, and natal homing of individuals back to Putah Creek in recent years. Although hatchery‐origin fish that strayed to Putah Creek to spawn dominated returns each year, this study documents life‐cycle completion required for the potential development of a self‐sustaining salmon population. This study demonstrates that targeted restoration and flow rehabilitation efforts can generate viable new salmon spawning habitat in dam‐controlled river systems, which could help mitigate habitat lost to dams and developments. Further, successful anadromous life‐cycle completion can occur in new spawning habitat within the first several generations, which will help inform efforts to restore or reintroduce salmon in other altered river systems.